Choosing lipid lowering statin in risk strategy of cardiovascular event prevention - A. Ya. Yvleva; L. A. Alekseeva; N. M. Poluboyarova (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To investigate low density lipoprotein cholesterol (LDL-CH) lowering effectiveness of atorvastatin (Torvacard; 20 mg/d) in patients with moderate hypercholesterolemia (HCH) after 4 and 12 weeks of treatment, together with standard hypolipidemic diet; to assess (%) target LDL-CH level achievement (<2,5 mmol/l, or 100 mg/dl) in patients of very high cardiovascular risk (risk category 1), receiving atorvastatin (Torvacard; 20 mg/d) for 12 weeks. Material and methods. The trial included 32 patients (20 men aged 40-68 years, 12 women aged 54-67 years). At baseline, all participants had LDL-CH level >3,4 mmol/l (130 mg/d) despite previous standard hypolipidemic diet for at least 4 weeks. Maximal LDL-CH level was as high as 4,5 mmol/l (175 mg/dl). Results. Tovacard lipid-lowering effect was completely manifested after 4 weeks: total CH level decreased by 32%, and at week 12 by 33%. LDL CH levels reduced by 44% and 46%, respectively. High density lipoprotein CH level increased by 6,3% at week 12. Plasma triglyceride levels decreased by 14% and 24% at weeks 4 and 12, respectively. Conclusion. Tovacard (20 mg/d) demonstrated high lipid lowering effectiveness. Atorvastatin generic, Torvacard, could be included into out-patient clinic medicine lists as an effective statin with optimal cost effectiveness and no need for dose titration.